2022
DOI: 10.1111/acem.14460
|View full text |Cite
|
Sign up to set email alerts
|

The clinical frailty scale predicts 1‐year mortality in emergency department patients aged 65 years and older

Abstract: Frailty is a state of increased vulnerability for poor resolution of homeostasis after a stressor event, so that frail individuals are at risk for adverse health outcomes and prolonged convalescence. 1 In the emergency department (ED), triage acuity predicts the outcomes of ED length of stay, hospitalization, intensive care unit (ICU) admission, and mortality within 30 days, 2 but may be ill-suited for prediction of adverse outcomes beyond this time frame. In a large Danish study, for example, abnormal vital s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 62 publications
(141 reference statements)
0
23
0
9
Order By: Relevance
“…Although the CFS classifies frailty into a 9-point scale, a dichotomous criterion that defines frailty as ≥5 is currently used. However, a recently published study by Rueegg et al 50 found that the 1year survival rate decreased with each increase in the CFS grade.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Although the CFS classifies frailty into a 9-point scale, a dichotomous criterion that defines frailty as ≥5 is currently used. However, a recently published study by Rueegg et al 50 found that the 1year survival rate decreased with each increase in the CFS grade.…”
Section: Discussionmentioning
confidence: 92%
“…Although the CFS classifies frailty into a 9‐point scale, a dichotomous criterion that defines frailty as ≥ 5 is currently used. However, a recently published study by Rueegg et al 50 found that the 1‐year survival rate decreased with each increase in the CFS grade. According to the results of their study, the restricted mean survival times of the CFS scores of 5 and 8 were 311 and 219 days, respectively; however, they are equally classified as just frail according to the current dichotomous interpretation.…”
Section: Discussionmentioning
confidence: 92%
“…The surprise question, a subjective estimation commonly used in palliative oncological patients [ 12 ], has been found to be associated with patients' mortality in the emergency department [ 13 ]. Age [ 8 ], comorbidities [ 14 ], and frailty status in patients aged 65 and older [ 15 ] have been identified as patient characteristics with prognostic value. While these scores, subjective estimation, and patient characteristics can be used to evaluate prognosis in specific patients and settings, we could not identify a validated score only assessing prognosis in unselected patients in the emergency department.…”
Section: Introductionmentioning
confidence: 99%
“…Eine Person mit Frailty ist einem erhöhten Risiko für Stürze, Hospitalisierung und Komplikationen bei invasiven/operativen Eingriffen ausgesetzt. Des Weiteren kommt es bei Patient*innen mit Frailty-Syndrom zu Pflegebedürftigkeit und einem reduzierten „Quality-of-Life-Index“ 7 8 9 .…”
Section: Introductionunclassified
“…Die Erfassung von Frailty hat daher eine hohe prognostische Relevanz in verschiedenen klinischen Bereichen wie der Anästhesieambulanz, der Intensivstation, der Notfallmedizin sowie in der Schmerz- und Palliativmedizin 8 , 9 , 12 . Hierdurch können gefährdete ältere Patient*innen bereits präoperativ identifiziert, geeignete prophylaktische Maßnahmen eingeleitet sowie Therapiemaßnahmen individuell angepasst werden.…”
Section: Introductionunclassified